Personalized fundraising: A field experiment on threshold matching of donations - Maja Adena; Steffen Huck (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2020)
We study a form of threshold matching where donations above a certain threshold are topped up with a fixed amount. We show theoretically that threshold matching can induce crowding in if appropriately personalized. In a field experiment, we explore how thresholds should be chosen depending on past donations. The optimal choice of thresholds is rather bold, approximately 60-75% above past donations. Additionally, we explore how thresholds should be set for new donors as a function of their personal characteristics and demonstrate the benefits of personalization as opposed to setting general thresholds applying to all recipients of a fundraising call.
Keywords: C93; D64; D12; 330; charitable giving; field experiments; matching donations; personalization